Всемирный доклад о наркотиках 2016 год - United Nations Office on Drugs; Crime (United Nations, 2016)
The World Drug Report provides a comprehensive overview of recent developments in the world's illicit drug markets. Chapter one of the World Drug Report 2016 provides a global overview of the latest statistics, trends and developments with respect to opiates, cocaine, cannabis and synthetic drugs, ranging from production to trafficking as well as consumption and the health consequences of drug use. Chapter two utilizes the Sustainable Development Goals framework to examine the interplay between the drugs phenomenon and the broader development context.